2019
DOI: 10.1111/dme.13984
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alimentación Normal con Ajuste de Insulina (ANAIS), a Spanish version of the DAFNE programme, in people with Type 1 diabetes: a randomized controlled parallel trial

Abstract: Aim To evaluate the effects of Alimentación Normal con Ajuste de Insulina (ANAIS), a group‐based, therapeutic education programme for Type 1 diabetes based on a flexible insulin regimen adjusted to the individual's food intake. Methods Participants with Type 1 diabetes and HbA1c levels of 53–86 mmol/mol (7–10%) were recruited from outpatient clinics at a tertiary care centre. They were randomized (using opaque, sealed envelopes, with a 2:1 treatment allocation ratio) to attend the training course immediately (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 27 publications
(38 reference statements)
0
36
0
Order By: Relevance
“…This is supported by another study with the same approach as DAFNE, but with subjects with moderate glycemic control that also failed to see any effects on HbA1c. 23 Another aspect is that FBA and RC received more active comparison treatment compared with the control group in DAFNE. In DAFNE, they also had positive results in 'present quality of life' and 'freedom to eat'.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by another study with the same approach as DAFNE, but with subjects with moderate glycemic control that also failed to see any effects on HbA1c. 23 Another aspect is that FBA and RC received more active comparison treatment compared with the control group in DAFNE. In DAFNE, they also had positive results in 'present quality of life' and 'freedom to eat'.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended glycemic target for patients with type 1 diabetes mellitus (T1DM) is an A1C <7.0% (RCT, General). All patients with T1DM should be systematically trained to adjust their insulin dose so that they can have flexible meals (RCT, General) [51][52][53][54]. The level of understanding following education and performance among patients with T1DM should be evaluated, and patients should receive regular feedback following a diagnosis of diabetes (Expert opinion, General).…”
Section: Antihyperglycemic Therapy For Adult Patients With Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…One study reported that 20.6% of participants incorporated continuous glucose monitoring (CGM) into diabetes self-management practices. 63 Participant comorbidities, which included retinopathy (n = 2), 44,61,67 neuropathy (n = 2), 44,61,67 chronic kidney disease, 61,67 hypertension (n = 1), 67 dyslipidemia (n = 2), 67,68 overweight/obesity (n = 1), 63 and depression (n = 2), 44,61,67 were reported in only 4 studies (5 reports).…”
Section: Resultsmentioning
confidence: 99%
“…63,68 One study did not clearly define the duration. 60 The frequency of encounters varied from daily in course-based education, 56,57,67 multiple times per week, 53 weekly, 62,66 multiple times per month, 44,61 monthly, 54,55,60,65 and every 3 to 4 months. 68 Other interventions utilized only 1 encounter, 64 individualized frequencies, 58 decreasing frequencies of participant contact over the intervention period, 59 or intervals with unspecified frequencies.…”
Section: Resultsmentioning
confidence: 99%